An den Hubs vorbei? Das Potenzial europäischer Sekundärflughäfen auf der Langstrecke. - Maertens, Sven (Deutscher Verkehrs-Verl., 2009)
Von einigen bedeutenderen Flughäfen abgesehen, kann die Masse der Sekundärflughäfen keine oder nur wenige Langstreckenflüge aufweisen, obwohl an vielen Standorten interkontinentalverkehrsspezifische Infrastrukturen vorgehalten werden. Die Ermittlung von Einflussfaktoren auf die Verteilung des nicht über die großen europäischen Hubs gehenden und daher als dezentral bezeichneten Langstreckenverkehrs zwischen sekundären Flughäfen ist Gegenstand einer Untersuchung, deren Hauptergebnisse im Beitrag vorgestellt werden.

In Europe, non-hub long haul air traffic is unevenly distributed between secondary airports. While there are a few airports, such as Manchester, offering many long haul flights, most secondary airports hardly ever welcome such services. The paper presents the main results of research project in which we discuss and test factors that might influence secondary airport choice of long haul carriers. Results indicate that the economic power of an airport's catchment area has a significant and strong positive influence on the supply of long haul flights, while a sufficient runway length alone does not automatically yield in many long haul services. As a consequence, long runways at most secondary airports in Europe are underutilized and thus not economically viable.
Missing the hubs.
Keywords: Verkehr; Luftverkehr; Flughafen; Verkehrsknoten; Standort; Verkehrsinfrastruktur; Verkehrswissenschaft; Verkehrsflughafen; Streckennetz; Fluggesellschaft; Luftverkehrsunternehmen; Empirische Untersuchung